2010
DOI: 10.1007/s10555-010-9252-1
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and breast cancer: status of leptin and adiponectin in pathological processes

Abstract: It is well recognized that obesity increases the risk of various cancers, including breast malignancies in postmenopausal women. Furthermore, obesity may adversely affect tumor progression, metastasis, and overall prognosis in both pre- and postmenopausal women with breast cancer. However, the precise mechanism(s) through which obesity acts is/are still elusive and this relationship has been the subject of much investigation and speculation. Recently, adipose tissue and its associated cytokine-like proteins, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
108
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(118 citation statements)
references
References 128 publications
5
108
0
3
Order By: Relevance
“…These data clearly signal that the dietary ratio of n-3:n-6 had an effect on adipose tissue function, a finding consistent with a number of reports. However, despite the fact that the mammary epithelium is imbedded in a subcutaneous fat pad and that leptin and adiponectin have been implicated in mammary carcinogenesis (45)(46)(47)(48)(49), no relationship was observed between the plasma concentration of these cytokines and mammary gland density. The effects of the 25:1 n-3:n-6 dietary ratio on leptin and adiponectin was confirmed in experiment 4 and was observed in the presence or absence of tamoxifen treatment ( Table 5).…”
Section: Discussionmentioning
confidence: 97%
“…These data clearly signal that the dietary ratio of n-3:n-6 had an effect on adipose tissue function, a finding consistent with a number of reports. However, despite the fact that the mammary epithelium is imbedded in a subcutaneous fat pad and that leptin and adiponectin have been implicated in mammary carcinogenesis (45)(46)(47)(48)(49), no relationship was observed between the plasma concentration of these cytokines and mammary gland density. The effects of the 25:1 n-3:n-6 dietary ratio on leptin and adiponectin was confirmed in experiment 4 and was observed in the presence or absence of tamoxifen treatment ( Table 5).…”
Section: Discussionmentioning
confidence: 97%
“…Several possible mechanisms have been suggested: i) Obese people often have increased levels of insulin and insulin-like growth factor-1 in their blood, which may promote the development of tumors (Belardi et al, 2013), ii) Adipose tissue produces hormones, called adipokines such as leptine and adiponectine, that may stimulate angiogenesis, growth of malignant cells (Grossmann et al, 2010;Khan et al, 2013) and that may modulate anti-tumor immune response (Catalan et al, 2013) iii) Finally, obesity is associated with elevated levels of pro-inflammatory cytokines (Harvey et al, 2011) which generate a low grade chronic inflammatory state that may be involved on cancer development (Hanahan and Weinberg, 2011;Ferguson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Risk of meningioma may also be influenced by the expression of sex hormones (3). Over the last decade, numerous types of tumors have been correlated with obesity, including colorectal and breast cancer, and uterus adenocarcinoma (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Leptin is a hormone synthesized by fatty tissue, and is responsible for the regulation of physiological processes, such as the modulation of appetite and thermogenesis, as well as pathological processes (9). A number of studies have demonstrated that the expression of the leptin receptor (LEPR, also known as ObR) correlates with the presence of leptin, suggesting that leptin-dependent malignancy may be regulated through autocrine and paracrine mechanisms (5,9). Leptin receptor isoforms are expressed throughout the central nervous system and a number of peripheral tissues, and six isoforms have been described previously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation